LATE PLEISTOCENE - EARLY - MIDDLE HOLOCENE TRANGRESSION IN MAINLAND AND CONTINENTAL SHELF OF VIET NAM - Nghi, Tran; Thanh, Dinh Xuan; Lan, Nguyen Thanh (Vietnam Journal of Marine Science and Technology, 2007)
Late Pleistocene - Holocene trangression started from 18 Ka (depth of 100 - 120 m watet) to 6 - 4 Ka (height of 4.5 - 6 m) according to maximum sea level. The transgressive process has been clearly recognized by 3 important shorelines as follows: - Shoreline situated in the depth of 50 - 60 m with the age of late Pleistocene (approximating 16 Ka). - Shoreline situated in the depth of 25 - 30 m with the age of Early - Middle Holocene (from 12 Ka to 10 Ka). - Shoreline situated in the elevation 4.5 - 6 m on marine terraces and notches in limestone mounts. The shorelines are characterized by following factors: - Abrasion - accumulation relief distributed in accordance with isobaths. - Existence of typical lithofacies: sandy bar, lagoonal clay, peat and coastal swamp, well rounded terrigenous and lateric marly pebble and gravel and rock fragments. -Marine terraces and notches of the same height on the mainland.